Why isn't there a one-size-fits-all approach for relapsed/refractory acute myeloid leukemia? Insights into different variables for decision-making. Issue 1 (March 2021) - Atallah, Ehab L.
Abstract: Relapsed refractory acute myeloid leukemia (R/R AML) has a poor prognosis. While the heterogeneity and diversity of R/R AML pose hurdles towards defining a standard of care, there have been various advances over the years. These, however, have added to the complexity of decision-making for R/R AML. This review has summarized evidence that will provide insights into factors that influence treatment choices in R/R AML and determine whether ongoing clinical trials can aid in identifying a standard approach for different sub-groups of patients.